ETIKA DAN AKUNTABILITAS GAYA KEPEMIMPINAN ETIS, STUDI KASUS PENGAMBILAN KEPUTUSAN PIMPINAN DALAM MENJAGA TRANSPARANSI PENYALURAN BANTUAN SOSIAL TERHADAP DAMPAK BENCANA BANJIR BANDANG DI KELURAHAN DADOK TUNGGUL HITAM - Aina Ilzahra; Alexa Rheva Anggela; Aminatussalsabila; Azahra Naima Puti Azka; Dafina Permata Dasti; Dinda Azzahra Putri; Elsya Dwi Septiyena; Syamsir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The flash flood disaster in Dadok Tunggul Hitam Village has placed the effectiveness of public leadership at a critical juncture, where moral integrity and accountability are vital instruments in the management of social assistance. This study aims to analyze the implementation of ethical leadership styles, evaluate the decision-making process in maintaining transparency, and measure the level of public accountability in the distribution of post-disaster social assistance. Using qualitative methods with a case study approach, this research explores how local leaders integrate the values of honesty and justice amidst the pressures of emergency situations. Data were collected through in-depth interviews with key informants such as the village head, village officials, volunteers, and affected communities, supported by participant observation and documentation studies. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and conclusion drawing.